Kinetics of Expression of Rhesus Monkey Rhadinovirus (RRV) and Identification and Characterization of a Polycistronic Transcript Encoding the RRV Orf50/Rta, RRV R8, and R8.1 Genes - DeWire, Scott M. (American Society for Microbiology, 2002)
Rhesus monkey rhadinovirus (RRV) is a close relative of Kaposi's sarcoma-associated herpesvirus (KSHV; human herpesvirus 8). RRV serves as an in vitro and an in vivo model for KSHV, and the mapping of its transcription program during lytic replication is significant since it represents de novo infection in the absence of stimulation with phorbol esters. Further, the RRV lytic system facilitates the making of recombinant viruses, and hence transcription profiling of the wild-type virus is important. Currently, the kinetics of lytic gene expression of RRV, the function of the RRV Orf50/Rta gene, and the presence of the RRV R8 and R8.1 genes are not known. This study details the transcription profile seen during RRV lytic replication and shows that RRV latency-associated nuclear antigen, viral FLIP (vFLIP), and vCyclin are transcribed during the RRV lytic phase. In addition, this study describes the identification of three new spliced products of the RRV Orf50, R8, and R8.1 genes, which are structural homologs of the KSHV Orf50, K8, and K8.1 genes, respectively. Characterization of the RRV Orf50 protein identifies it as a strong transcriptional transactivator capable of activating three early RRV promoters. Interestingly, the KSHV Orf50 transactivator can also activate these simian virus promoters, suggesting that there exists a conservation of gene function between the key transcription factors of KSHV and RRV.